Study of the corrosive effect of chloride and bromide on samples of carbon steel and stainless steel (Research, Society and Development, 2019)
This work shows the analysis of the corrosive effect on carbon steel and stainless steel in aqueous medium, in order to compare the damages caused to these metals through the contact with ions which are present in the environment, as well as to measure the price-performance ratio of the use of these materials, since the corrosion resistance is linked to the commercial value of these metals. For this purpose, the methodology used was the corrosion test in SAE 1015 carbon steel and ACE P399B stainless steel, which were exposed to diluted solutions of sodium chloride 0,1 mol.L-1, potassium bromide 0,1 mol.L-1 and one containing 50% sodium chloride and 50% potassium bromide 0,1 mol.L-1, then the variation of mass of each metal sample in these different environments as well as their respective corrosion rate were verified. The results showed that although stainless steel suffers corrotion, carbon steel is the most affected by the ions present in such environment. In addition, the sodium chloride solution proved to be the most harmful medium for both steels, which is due to the release of chloride ions in these metals. Seen in these terms, as expected, stainless steel is the most resistant material to corrosion. However, in comparative terms, it did not show an exorbitant difference in relation to carbon steel, and can, therefore, be substituted by it in certain situations, in which the price-performance ratio is demanded.